Sulfur conversion and distribution during supercritical water gasification of sewage sludge. (April 2021) - Yan, Mi; Feng, Hongyu; Zheng, Rendong; Yu, Caimeng; Hantoko, Dwi; Zhou, Zhihao; Zhang, Yan; Kanchanatip, Ekkachai
Abstract: In order to study the transformation and distribution of sulfur element during supercritical water gasification (SCWG) of sewage sludge, sulfur contained products in different phase were detected in batch reactor. The XPS analysis showed that organic sulfur was the main part of sulfur compounds in sewage sludge. On the other hand, inorganic sulfur was dominated by SiS2, and SiS2 was subsequently converted into SiO2 and H2 S during SCWG. The increase of temperature promoted H2 S and SO2 yield but reduced their concentration. The addition of KOH could reduce the yield and concentration of H2 S and SO2 . The minimum concentration of H2 S and SO2 was observed at 450 °C with KOH addition, which was 1313.94 ppm and 698.03 ppm, respectively. Sulfur compound in liquid was mainly found in the form of sulfate and its concentration decreased with increasing temperature. Highlights: Sulfur conversion and distribution during SCWG of sewage sludge was studied. Sulfur compound in sludge was decomposed into H2 S and SO2 . SCWG temperature increased the yields of H2 S and SO2 . The addition of KOH reduced the yields and concentrations of H2 S and SO2 in syngas. SCWG can convert part of sulfur compound into sulfate and dissolve in liquid.